(untitled) (Applied Biological Research, 2018)
The present investigations were carried out at Fruit Research Farm, PAU, Ludhiana (India) with an aim to study the effects of foliar sprays of amino acids on fruit yield, quality and biochemical properties in peach [Prunus persica (L.) Batsch] and to identify the ideal time and dose of application. The 6-year old peach cv. ‘Florda Prince’ trees were sprayed with 0.25 and 0.50% amino acids (Peptone P1 023), 7 and 14 days after full bloom and the sprayswere repeated after 15 and 30 days. The highest yield (53.92 kg tree-1), TSS content (12.2°Brix), TSS/acid ratio (18.39) and total sugars content (5.15%) were recorded in treatment receiving double spray of amino acids (2 sprays @ 0.50% 14 DAFB and 15 days later). This treatment recorded maximumanthocyanin content (7.86 mg 100 g-1fw), β-carotene content (0.97 mg 100 g-1 fw of pulp) and total phenolic contents (66.24 mg GAE 100 g-1fw) as compared to the control. All the double-spray amino acid treatments improved fruit characteristics as compared to control and other treatments.